2017
DOI: 10.1080/07388551.2017.1312275
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the research of celery, an important Apiaceae vegetable crop

Abstract: Celery (Apium graveolens L.), one of the most important vegetables in Apiaceae family, is cultivated worldwide and utilized in food and cosmetic industries because it is an excellent source of vitamins, phenolic compounds, volatile oils and other nutrients. Celery extracts possess various medicinal properties, such as antibacterial, anti-inflammatory and lowering blood glucose and serum lipid levels. With the rapid advancements in molecular biology and sequencing technology, studies on celery have been perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 97 publications
2
66
0
2
Order By: Relevance
“…With the continuous development of sequencing technology, whole-genome sequencing has been carried out in increasing numbers of species, providing a great deal of biological information for genome mapping, functional gene mining and molecular breeding. Celery is normally classified as a cool-season vegetable and widely consumed around the world, and the cultivation history of celery is longer than 2000 years 2,3 . To understand the genetic system and evolution of Apiaceae, we sequenced the genome of celery, which offers new insights and provides resources for molecular breeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the continuous development of sequencing technology, whole-genome sequencing has been carried out in increasing numbers of species, providing a great deal of biological information for genome mapping, functional gene mining and molecular breeding. Celery is normally classified as a cool-season vegetable and widely consumed around the world, and the cultivation history of celery is longer than 2000 years 2,3 . To understand the genetic system and evolution of Apiaceae, we sequenced the genome of celery, which offers new insights and provides resources for molecular breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin is one of the most important flavonoid compounds and exhibits a variety of biological activities and pharmacological effects 3 . Compared with other plants, celery has a higher content of apigenin 6,8 .…”
Section: Apigenin Biosynthesis Pathway In Celerymentioning
confidence: 99%
See 1 more Smart Citation
“…Celery ( Apium graveolens ) is a biennial plant in the family of Apiaceae, which originated from the Mediterranean basin and the Middle East (Li et al , ). Celery is cultivated worldwide and distinguished as a healthy food for its low energy density and bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…After determining the pharmacokinetic properties of a drug,we needed to nd the target genes for drug action.Many articles had shown that compounds extracted from plants were inextricably linked to genes or proteins [32][33][34].To this end,we used CTD to predict 28 genes online (Table 2). Since 6 genes had been reported in our previous research,a total of 34 target genes were in our study.To further explored the function of these 34 genes,we used the GeneMANIA online tool to prove their co-expression,physical communication,co-localization and other functional information (Fig.…”
Section: Discussionmentioning
confidence: 99%